Profesionalisme Tenaga Kepustakaan dalam Penguasaan Teknologi Informasi di Sman 12 Banda Aceh - Ismail Anshari; Yusnaini Yusnaini (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
This research is motivated by the lack of professional librarian in their field. There is only one librarian who actually comes from the library science department. The professionalism of the librarian is the implementation of library activities based on the ability of knowledge, experience, skills in managing and developing the implementation of work in the field of librarianship and other related activities independently. This research is entitled